Does San Francisco's Community Justice Center Reduce Criminal Recidivism? - Kilmer, Beau (RAND Corporation, 2014)
Community courts aim to improve outcomes by addressing factors linked to criminal behavior with access to treatment and services, and by emphasizing ties to a specific neighborhood. In 2009, San Francisco opened the Community Justice Center (CJC), a community court serving a traditionally high-crime area. This report examines whether the CJC reduces the risk of rearrest when compared to more traditional approaches for addressing arrestees.